Advances in cognitive neurodynamics (VI) : proceedings of the sixth International Conference on Cognitive Neurodynamics -- 2017 /: proceedings of the sixth International Conference on Cognitive Neurodynamics -- 2017. (2018) - Unknown
No abstract available